C-reactive protein as a potential biomarker for disease progression in dengue: a multi-country observational study - Vuong, NL; Le Duyen, HT; Lam, PK; Tam, DTH; Vinh Chau, NV; Kinh, NV; Chanpheaktra, N; Lum, LCS; Pleités, E; Jones, NK; Simmons, CP; Rosenberger, K; et al. (BioMed Central, 2020)
BACKGROUND: Dengue infection can cause a wide spectrum of clinical outcomes. The severe clinical manifestations occur sufficiently late in the disease course, during day 4-6 of illness, to allow a window of opportunity for risk stratification. Markers of inflammation may be useful biomarkers. We investigated the value of C-reactive protein (CRP) measured early on illness days 1-3 to predict dengue disease outcome and the difference in CRP levels between dengue and other febrile illnesses (OFI). METHOD: We performed a nested case-control study using the clinical data and samples collected from the IDAMS-consortium multi-country study. This was a prospective multi-center observational study that enrolled almost 8000 participants presenting with a dengue-like illness to outpatient facilities in 8 countries across Asia and Latin America. Predefined severity definitions of severe and intermediate dengue were used as the primary outcomes. A total of 281 cases with severe/intermediate dengue were compared to 836 uncomplicated dengue patients as controls (ratio 1:3), and also 394 patients with OFI. RESULTS: In patients with confirmed dengue, median (interquartile range) of CRP level within the first 3 days was 30.2 mg/L (12.4-61.2 mg/L) (uncomplicated dengue, 28.6 (10.5-58.9); severe or intermediate dengue, 34.0 (17.4-71.8)). Higher CRP levels in the first 3 days of illness were associated with a higher risk of severe or intermediate outcome (OR 1.17, 95% CI 1.07-1.29), especially in children. Higher CRP levels, exceeding 30 mg/L, also associated with hospitalization (OR 1.37, 95% CI 1.14-1.64) and longer fever clearance time (HR 0.84, 95% CI 0.76-0.93), especially in adults. CRP levels in patients with dengue were higher than patients with potential viral infection but lower than patients with potential bacterial infection, resulting in a quadratic association between dengue diagnosis and CRP, with levels of approximately 30 mg/L associated with the highest risk of having dengue. CRP had a positive correlation with total white cell count and neutrophils and negative correlation with lymphocytes, but did not correlate with liver transaminases, albumin, or platelet nadir. CONCLUSIONS: In summary, CRP measured in the first 3 days of illness could be a useful biomarker for early dengue risk prediction and may assist differentiating dengue from other febrile illnesses.